2013
DOI: 10.3389/fnagi.2013.00086
|View full text |Cite
|
Sign up to set email alerts
|

Age-dependent effect of Alzheimer’s risk variant of CLU on EEG alpha rhythm in non-demented adults

Abstract: Polymorphism in the genomic region harboring the CLU gene (rs11136000) has been associated with the risk for Alzheimer’s disease (AD). CLU C allele is assumed to confer risk for AD and the allele T may have a protective effect. We investigated the influence of the AD-associated CLU genotype on a common neurophysiological trait of brain activity (resting-state alpha-rhythm activity) in non-demented adults and elucidated whether this influence is modified over the course of aging. We examined quantitative electr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 80 publications
2
31
0
2
Order By: Relevance
“…The homozygous presence of the AD risk variant CLU CC in asymptomatic subjects is associated with an increase of Alpha-3 (11-13 Hz) and Alpha-1 (7.5-9 Hz) power. The Alpha-3, which is close to our Alpha-2, is also higher in young subjects and lower in old subjects [65]. The Apolipoprotein E (ApoE) ε4 allele is the greatest genetic susceptibility factor for AD and has been studied in carriers with AD and MCI using EEG [66][67][68][69][70], having been also reported anomalies for Alpha and Theta band at resting state related to slowing of EEG [71,72].…”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations
“…The homozygous presence of the AD risk variant CLU CC in asymptomatic subjects is associated with an increase of Alpha-3 (11-13 Hz) and Alpha-1 (7.5-9 Hz) power. The Alpha-3, which is close to our Alpha-2, is also higher in young subjects and lower in old subjects [65]. The Apolipoprotein E (ApoE) ε4 allele is the greatest genetic susceptibility factor for AD and has been studied in carriers with AD and MCI using EEG [66][67][68][69][70], having been also reported anomalies for Alpha and Theta band at resting state related to slowing of EEG [71,72].…”
Section: Discussionsupporting
confidence: 63%
“…Golob et al [64] reported differences in ERP acquired during a target detection task in asymptomatic subjects carriers of PSEN1 mutation (A431E substitution = 14, L235V substitution = 5) and APP mutation (V717I substitution). The CLU genotype, that is related to risk for AD, exerts a significant effect on Alpha absolute power in resting state for asymptomatic subjects [65]. The homozygous presence of the AD risk variant CLU CC in asymptomatic subjects is associated with an increase of Alpha-3 (11-13 Hz) and Alpha-1 (7.5-9 Hz) power.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent evidence suggests that genetic factors of pathological aging like clusterin ( CLU ) gene polymorphisms and the apolipoprotein E ε4 ( APOE4 ) mutation may affect upper alpha absolute power in nondemented elderly individuals [27], or reduce the amplitude of the posterior-dominant alpha rhythm in early AD [28, 29]. Taken together, these alpha frequency findings suggest that the genotype is associated with age-related preclinical dysregulation of hippocampal function and contributes to AD pathophysiology.…”
Section: Aging and Cortical Oscillationsmentioning
confidence: 99%
“…Behaviorally, this was reflected in faster response times in identifying happy faces for older A homozygotes. Further, an electroencephalography study examined the association between the AD-related clusterin (CLU; rs11136000) polymorphism and resting-state alpha-rhythm activity in healthy non-carriers of the APOE ε4 allele (Ponomareva et al 2013). The CLU CC risk variant was associated with an increase of alpha activity only in older adults (50-80 years), whereas there were no genetic effects in younger adults (20-50 years).…”
Section: Miscellaneous Genesmentioning
confidence: 99%